2018
DOI: 10.14742/ajet.3843
|View full text |Cite
|
Sign up to set email alerts
|

Debating the use of social media in higher education in Australasia: Where are we now?

Abstract: The integration of social media into higher education is having a significant impact on learning and teaching. As they become enmeshed in the fabric of academia, they are also becoming a site of contestation, especially in relation to teaching and learning. This research paper explores the key issues dominating current debates about the use of social media in higher education in Australasia. By exploring themes emerging from a debate around the use of social media in higher education in Australasia, it integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…The study by [62], while highlighting advantages such as increased interest in taking online courses, improved communication skills, and reduced dropout rates, also reported on ethical concerns, and how excessive use might result in isolation in real life, and other health-related issues, such as stress, anxiety, and depression. To find the right balance, educational technology specialists suggest that it is necessary for institutions to have social media strategies and policies, to guide effective use and beneficial outcomes, while mitigating potential risks to students and educators [63].…”
Section: Discussionmentioning
confidence: 99%
“…The study by [62], while highlighting advantages such as increased interest in taking online courses, improved communication skills, and reduced dropout rates, also reported on ethical concerns, and how excessive use might result in isolation in real life, and other health-related issues, such as stress, anxiety, and depression. To find the right balance, educational technology specialists suggest that it is necessary for institutions to have social media strategies and policies, to guide effective use and beneficial outcomes, while mitigating potential risks to students and educators [63].…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out by Özer et al (2014) investigated the effect of SM on the academic performance of students in the USA and Europe, where European students prefer using SM for educational purposes and having a positive effect on their academic performances, more than American students. Research from another part of the world, Australasia, explored the themes emerged from a debate (Twitter, Periscope) about the use of SM in HE (Willems et al 2018). It was found that there is a direct significant relationship between the use of SM and the academic success of the students (Maqableh et al 2015).…”
Section: Use Of Sm As a Tool For Educationmentioning
confidence: 99%
“…On the other hand, varied research (Abdelraheem 2013;BrckaLorenz, Cervera, and Garver 2010) claims that when the institutional guidance is not provided, the students in HE use SM for more social purposes than academic. In another research, it is discovered that there are risks of both adapting and ignoring SM (Willems et al 2018). The reality of SM being available in education cannot be ignored; instead, they suggest that institutions should create a clear and understandable SM policy that would help its use in education.…”
Section: Use Of Sm As a Tool For Educationmentioning
confidence: 99%
“…In general, students utilize social media regularly in their daily lives and by incorporating this technology into the classroom, instructors can meet students where they are and where they are comfortable. By not doing so, it may artificially limit teaching capacity and also lead to a greater divide between higher education institutions and the public at large (Willems et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using video production can also increase students" presentation skills through organization, delivery techniques, and speech content development (Liu, 2016). information and communication technology in education and digital literacy has been identified as an important skill that should be implemented as a graduate outcome (Willems et al, 2018). To our knowledge, virtually no studies have concentrated on the integration and analysis of multiple modes of technology within a higher education classroom.…”
Section: Introductionmentioning
confidence: 99%